Modulation of Solid-State Aggregation of Square-Planar Pt(II) Based Emitters: Enabling Highly Efficient Deep-Red/Near Infrared Electroluminescence - Wen Cheng Chen (2020)
© 2020 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim The design of square-planar Pt(II) complexes with highly efficient solid-state near infrared (NIR) luminescence for electroluminescence is attractive but challenging. This study presents the fine-turning of excited-state properties and application of a series of isoquinolinyl pyrazolate Pt(II) complexes that are modulated by steric demanding substituents. It reveals that the bulky substituents do not always disfavor metallophilic Pt···Pt interactions. Instead, π–π stacking among chelates, which are fine-tuned by the associated substituents, also exerts strong influence to the metal-metal-to-ligand charge transfer (MMLCT) transition character. Theoretical calculations indicate that Pt···Pt contacts become more relevant in the trimers rather than the dimers, especially in their T1 states, associated with a change from mixed 3LC/3MLCT transition in the monomer/dimer to mixed 3LC/3MMLCT transition character in the trimer. Electroluminescence devices affording intense deep-red/NIR emission (near 670 nm) with unprecedentedly high external quantum efficiency over 30% are demonstrated. This work provides deep insights into formation MMLCT transition of square-planar Pt(II) complexes and efficient molecular design for deep-red/NIR electroluminescence.